Women's Rights in Islamic Culture: A Bibliometric Analysis of Trends, Influential Authors, and Institutional Contributions (1969–2023) - Jobeda Khanom; Md. Tarequl Islam; Mahmudulhassan (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: This study aims to analyze bibliometric trends, influential authors, and institutional contributions in the study of women's rights in Islamic culture from 1969 to 2023. The research examines the evolution, impact, and emerging directions in this research landscape through bibliometric analysis based on Scopus data. The data were analyzed to identify annual publication trends, leading academic sources, key authors, institutional affiliations, and regional contributions. Theoretical framework: The theoretical framework highlights a collaborative and interdisciplinary approach to the study of women's rights, focusing on a quantitative analysis of publication trends and contributions from key actors. Literature Review: The reviewed literature includes seminal works such as Kaya (2015) and Sattin (2016), which have significant impacts as evidenced by high citation counts. Methods: The methodology employs bibliometric analysis using specialized software to map trends, evaluate publication volumes, identify leading authors, and analyze contributions by countries and institutions. Results: The findings reveal a significant increase in research efforts since the 2000s, with a peak in productivity in recent years. Authors such as Tønnessen, L., and Spierings, N. emerged as key contributors, while journals like Muslim World and Women's Studies were identified as primary channels. The United States and the United Kingdom stood out as major contributing countries, supported by institutions like Radboud Universiteit. Implications: The implications of this study include recommendations for researchers and policymakers to prioritize future research, particularly in identifying underexplored areas. Novelty: The originality of this research lies in its comprehensive mapping of the bibliometric trajectory and identification of underrepresented research areas. These findings offer valuable insights for advancing studies on women's rights in Islamic culture, fostering cross-disciplinary and cross-regional collaborations.